Fiscal Adjustment for Stability and Growth. (Policy Papers; Policy Paper, 2006)
This paper aims to inform policymakers, and other interested parties, about the IMF's approach to fiscal adjustment. The approach focuses on the role of sound and sustainable government finances in promoting macroeconomic stability and growth. Achieving, and maintaining, such a fiscal position often requires adjusting fiscal policy, as well as strengthening fiscal institutions. Fiscal adjustment may involve either tightening or loosening the fiscal stance, depending on individual country circumstances.